The Model for Integrating Medicine and Psychology as a Valid Theoretical Framework for Polycystic Ovary Syndrome - Narula, Ashima; Mahapatra, Mamata (International Journal of Psychosocial Rehabilitation, 2020)
Polycystic Ovary Syndrome is a hormonal condition common in women of reproductive age. The types of symptoms, severity, chronicity vary in every woman. The study aimed at evaluating the applicability of the model for integrating medicine and psychology for PCOS.Due to lack of researches in PCOS in relation to psychological aspects in Indian context, this review will draw attention to issue in diagnosis and treatment of comorbid problems associated with PCOS. Researches published in various databases like PubMed, google scholar, web of sciences were reviewed according to the factors associated to the model. The adverse physical and psychosocial effects may lead to unhealthy behaviour and impact health related quality of life. Medical professionals have an opportunity to educate women about the disease process of PCOS and to implement strategies to treat these patients physical and psychosocial problems to improve their wellbeing for a lifetime.